Nationwide screening of Fabry disease in patients with hypertrophic cardiomyopathy in Czech Republic - Zemánek, David; Januška, Jaroslav; Honěk, Tomáš; Čurila, Karol; Kubánek, Miloš; Šindelářová, Štěpánka; Zahálková, Lucie; Klofáč, Petr; Laštůvková, Eliška; Lichnerová, Eva; Aiglová, Renata; Lhotský, Jan; et al. (ESC heart failure, 2022)
AIMS: Fabry disease (FD) is a rare X-linked genetic disorder caused by α-galactosidase A (AGALA) deficiency. Whereas 'classic' variant has multisystemic manifestation, the more recently described 'later-onset' variant is characterized by predominant cardiac involvement that often mimics hypertrophic cardiomyopathy (HCM). METHODS AND RESULTS: Consecutive unrelated patients with HCM were screened for FD in 16 (out of 17) cardiac centres in the Czech Republic covering specialized cardiology care from June 2017 to December 2018. AGALA activity and globotriaosylsphingosine (lyso-Gb3 ) levels were measured in all subjects using the dry blood spot method. FD was suspected in male patients with AGALA activity <1.2 μmol/h/L and in females with either low AGALA activity or lyso-Gb3 > 3.5 ng/mL. Positive screening results were confirmed by genetic testing. We evaluated 589 patients (390 males, 66%) with HCM (mean maximal myocardial thickness 19.1 ± 4.3 mm). The average age was 58.4 ± 14.7 years. In total, 17 patients (11 males, 6 females) had a positive screening result, and subsequently, six of them (four males and two females) had a genetically confirmed pathogenic GLA mutation (total prevalence of 1.02%). Five of these patients were carrying the p.N215S mutation known to cause a typical later-onset cardiac FD. CONCLUSIONS: We confirmed the prevalence of FD repeatedly reported in previous screening programmes (approximately 1% irrespective of gender) in a non-selected HCM population in Central Europe. Our findings advocate a routine screening for FD in all adult patients with HCM phenotype including both genders. The dry blood spot method used led to identification of clearly pathogenic variants.
Keywords: dospělí; Genetic Testing; Humans; lidé středního věku; Middle Aged; Fabry Disease; Fabryho nemoc; Czech Republic; alfa-galaktosidasa; mužské pohlaví; Česká republika; Adult; Cardiomyopathy, Hypertrophic; ženské pohlaví; lidé; hypertrofická kardiomyopatie; alpha-Galactosidase; Aged; senioři; genetické testování; Male; Female